On the applicability of the improved imbedded drop retraction method for estimation of the interfacial tension in polymer melt blends - A. S. Pankratov; Yu. P. Miroshnikov (Тонкие химические технологии)
The applicability of the improved imbedded fiber retraction method for measuring the interfacial tension in plastic/plastic, elastomer/plastic and elastomer/elastomer polymer melt blends has been analyzed experimentally. The technique was shown to be quite adequate for plastic/plastic combinations but failed for blends including elastomers .